Detection of Cyberbullying Using Bernoulli Restricted Boltzmann Machine and Multilayer Perceptron Neural Networks - Lezama Sánchez, Ana Laura; Tovar Vidal, Mireya (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
This paper introduces a model that detects harassment cases across different social media platforms using natural language processing and deep learning. Therefore, this model forms part of a system that can identify this problem in various texts.